Cobalt-doped cotton-derived carbon for enhancing the performance of antimony-removing microbial electrolysis cells - Leyi Chen; Haowen He; Jiayuan Huang; Haifeng Cheng; Chengjun Guo; Xing Chen; Xing Lu; Kengqiang Zhong; Jingyi Wang; Jiaqian Zhang; Meng Li; Lei Huang; et al. (Journal of Water Process Engineering, 2026)

Water-soluble matter mediated phototransformation of guaiacol leading to formation of aqueous secondary organic aerosol: Mechanism and kinetics - Jiayi Wang; Rui Zeng; Jun He; Chengjun Wang (Journal of Environmental Sciences, 2026)

Formation and application of soybean protein amyloid fibril-dextran-epigallocatechin gallate nanoparticles for interfacial engineering of lycopene-loaded Pickering emulsions - Changling Wu; Jie Hou; David Julian McClements; Li Li; Zhaogui Chen; Chengjun Liao; Kaixi Chen; Guangbiao Yan; Hao Hu; Guanyu Fang; Zhiping He; Xingquan Liu; et al. (Food Chemistry, 2026)

Unraveling microscopic dielectric response of liquid-liquid phase separation via electrochemical impedance spectroscopy combined with distribution of relaxation times - Jie He; Jinming Liang; Kai Liu; Bai Chen; Wanyi Ye; Xiuli Wu; Siqi Zhu; Zhenqiang Chen; Chengjun Zhu; Jiafeng Yao (Chemical Engineering Journal, 2026)

Migration and transformation of antimony during Fe(II)-induced ferrihydrite recrystallization under anaerobic conditions - Chengjun Zhang; Mengchang He; Huiji Liu; Matthew I. Leybourne; Tangfu Xiao (Applied Geochemistry, 2026)

Release of antimony from Sb(V) incorporated iron oxides during oxalate-promoted recrystallization under aerobic conditions - Chengjun Zhang; Mengchang He; Tangfu Xiao; Huiji Liu (Environmental Research, 2026)

Steel plate-UHPC composite strengthening method for large-span prestressed concrete box girder bridges: Simulation, optimization, and case study - Tao Sun; Weikun He; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu; Hua Zhao (Engineering Structures, 2026)

Influence of interface geometry on interfacial shear between precast UHPC and cast-in-place normal-strength concrete: Experimental and analytical investigation - Lei Tu; Weikun He; Hua Zhao; Chengjun Tan; Jiahe An; Junde Hu; Lizhi Lu (Engineering Structures, 2026)

An interpretable deep learning framework for UHPC dry joint shear strength prediction under small sample regimes - Jingqi Cao; Weikun He; Chengjun Tan; Lei Tu; Suiwen Wu; Jiahe An; Junde Hu; Hua Zhao (Engineering Structures, 2026)

Defect-rich carbon induced built-in electric fields within molybdenum-based metal-organic framework catalysts for enhanced activity and stability in oxidative desulfurization - Juncong Zou; Yang Yan; Shanying He; Chengjun Ge; Dexin Wang; Chunping Yang (Journal of Hazardous Materials, 2026)

Airborne microplastics in China: Assessing urbanization, weather factors and policy implications from the nationwide study - Taiseer Hussain Nafea; Yuyao Xu; Faith Ka Shun Chan; Yaoyang Xu; Hang Xiao; Honghui Xu; Dongsheng Ji; Chengjun Wang; John L. Zhou; Jun He (Journal of Cleaner Production, 2026)

Ready-to-eat beef steaks prepared by superheated steam: from texture and flavor to storage stability - Jiyuan He; Lunzhou Lin; Jiebin Cai; Chengjun Liu; Yaming Xiao; Yajie Shen; Binxiong Liu; Ting Fang (International Journal of Gastronomy and Food Science, 2025)

Overcoming uranium re-dissociation in microbial electrolysis cells: Hydrogen-bond mediated reduction mechanisms in sulfate-reducing bacteria systems - Leyi Chen; Yuchen Yang; Kengqiang Zhong; Xing Lu; Haowen He; Xing Chen; Luoyi Han; Chengjun Guo; Meng Li; Lei Huang; Jia Yan; Diyun Chen; et al. (Chemical Engineering Journal, 2025)

Harnessing nanomaterial-driven electron transfer for enhanced uranium recovery and toxicity mitigation in bioelectrochemical systems - Meng Li; Leyi Chen; Kengqiang Zhong; Haowen He; Xing Chen; Xing Lu; Chengjun Guo; Luoyi Han; Ziyin Xia; Chenxi Li; Jingyi Wang; Wei Han; et al. (Bioresource Technology, 2025)

Neural Network-Based Ship Power Load Forecasting - Haozheng Liu; Chengjun Qiu; Wei Qu; Wei He; Yuan Zhuang; Puze Li; Huili Hao; Wenhao Wang; Zizi Zhao; Jiahua Su (Journal of Marine Science and Engineering, 2025)
This study combines an experimental semi-physical simulation model of an electric propulsion tugboat with four different neural networks to create a real-time simulation model for forecasting total power loads with small samples. The results of repeated experiments demonstrate that the BP neural network effectively forecasts the power load. Subsequently, addressing the limitations of traditional BP neural networks, an optimization approach employing an enhanced particle swarm algorithm and attention mechanism was developed, thereby improving the model’s prediction accuracy and robustness. The experiment shows that the improved prediction model achieves an R2 value of 97.42%, demonstrating its effectiveness in forecasting changes in the short-term power load of ships as parameters change. In actual operation, ships can allocate power reasonably and in a timely manner according to the load forecast results, thereby improving the efficiency of the power grid.

Decoding PM2.5 oxidative potential in Ningbo, China: Key chemicals, sources, and health risks via dual-assay and machine learning - Lord Famiyeh; Ke Chen; Jingsha Xu; Fiseha Berhanu Tesema; Mosses Solomon; Dongsheng Ji; Honghui Xu; Chengjun Wang; Qingjun Guo; Conghua Wen; John L. Zhou; Jun He (Journal of Hazardous Materials, 2025)

Autochthonous DOM governs the occurrence and methylation of mercury-containing nanoparticles in urban river water: An integrated study of field investigations and laboratory experiments - Jin Zhang; Pei Lei; Huan Zhong; Nan Zou; Martin Tsz-Ki Tsui; Carl P.J. Mitchell; Chengjun Li; Weiping Cai; Han Meng; Huan He; Fei Dang (Journal of Hazardous Materials, 2025)

Occurrence, hydrolysis and photodegradation of phthalate esters in urban atmospheric aqueous aerosol in Wuhan City - Xinyue Zhao; Siyu Liu; Lina Wang; Li Yang; Jun He; Chengjun Wang (Environmental Pollution, 2025)

Comprehensive review on in vitro bioaccessibility of mercury in various foodstuffs - Yu Gong; Chengjun Li; Fei He; Feng Ge; Yongming Ju; Huan Zhong; Weixin Li (Journal of Hazardous Materials, 2025)

Fast decomposition of typical endocrine disturbing compounds in microdroplets under sunlight irradiation in the presence of ozone - Siyu Liu; Xinyue Zhao; Yaobin Ding; Lina Wang; Yiyang Li; Jun He; Chengjun Wang (Chemosphere, 2025)

Low-temperature catalytic oxidation of toluene using CeO2@MIL-101(Fe): Stability against water and SO2 - David Murindababisha; Abubakar Yusuf; Kien-Woh Kow; Yong Sun; Run Pan; Yong Ren; George Zheng Chen; Jianrong Li; Chengjun Wang; Jun He (Process Safety and Environmental Protection, 2025)

Detachment fault system in the Zedang ophiolite of southern Tibet: New insights into the evolution of the neo-Tethys ocean - Yuan Li; Ruibao Li; Chengjun Liu; Jian Zhang; Duoji Ciren; Xiao Zhou; Zhenkai He; Jingsui Yang (Journal of Asian Earth Sciences, 2025)

Field Experiments and a Meta‐Analysis Reveal a Minor Influence of Nitrogen Addition on Phosphorus Fractions in Forests - Qingshui Yu; Xiaofeng Ni; Frank Hagedorn; Josep Penuelas; Jordi Sardans; Mai‐He Li; Suhui Ma; Jianxiao Zhu; Di Tian; Chengyang Zheng; Jiangling Zhu; Chengjun Ji; et al. (Global Change Biology, 2025)
Anthropogenic nitrogen (N) inputs can significantly impact nutrient cycling and ecosystem functioning in terrestrial ecosystems. However, the effects of N addition on phosphorus (P) cycling processes in forest ecosystems remain unclear. In this study, we combined data from a long‐term (11‐year) N addition experiment across seven different forests ranging from temperate to tropical biomes, with a global meta‐analysis from 88 relevant publications, to investigate the responses of P cycling‐related variables to N inputs in forest ecosystems. We found that N addition had little effect on most P cycling‐related variables (e.g., leaf P, soil total P, soil available P, soil P fractions, and microbial biomass P) across the studied forest ecosystems. The meta‐analysis highlighted that N‐induced changes in P cycling were highly variable. Only a few variables, such as the leaf P concentration and the activity of soil acid phosphatase, presented significant responses to N addition and changed with climatic zone and the amount and duration of N inputs. Our study suggests that P cycling processes in forest ecosystems remain largely unaffected by N inputs. Our findings contribute to a better understanding and prediction of biogeochemical cycles in the context of N deposition related to anthropogenic activities and global climate change.

Status of management and mitigation of microplastic pollution - Taiseer Hussain Nafea; Faith Ka Shun Chan; Honghui Xu; Chengjun Wang; Hang Xiao; Jun He (Critical Reviews in Environmental Science and Technology, 2024)

Biogas slurry-derived dissolved organic matter inhibited oxytetracycline adsorption by tropical agricultural soils - Hui Chen; Lingfei Yin; Yuan He; Liangtai Bai; Yuejun Wu; Yuanyuan Zhao; Febelyn Reguyal; Ajit K. Sarmah; Xing Yang; Chengjun Ge; Hailong Wang (Science of The Total Environment, 2024)

Study of pyrene-based covalent organic frameworks for efficient photocatalytic oxidation of low-concentration NO - Zhiyu Xiao; Yong Ren; George Zheng Chen; Yong Sun; Chengjun Wang; Jun He (Journal of Environmental Chemical Engineering, 2024)

High-Efficiency NO conversion via In-Situ grown covalent organic framework on g-C3N4 nanosheets with Single-Atom platinum photocatalyst - Zhiyu Xiao; Abubakar Yusuf; Yong Ren; George Zheng Chen; Chengjun Wang; Jun He (Chemical Engineering Journal, 2024)

Impact of Spatial Inhomogeneity in Atmospheric CO2 Concentration on Surface Air Temperature Variations - Chengjun Xie; Tongwen Wu; Jie Zhang; Weihua Jie; Mengzhe Zheng; He Zhao (Journal of Meteorological Research, 2024)

Microplastics Aloft: A comprehensive exploration of sources, transport, variations, interactions and their implications on human health in the atmospheric realm - Taiseer Hussain Nafea; Faith Ka Shun Chan; Yuyao Xu; Chengjun Wang; Xiaoyuan Wang; Wenlong Zhao; Dongsheng Ji; Hang Xiao; Jun He (Earth-Science Reviews, 2024)

Practical four-electron zinc-iodine aqueous batteries enabled by orbital hybridization induced adsorption-catalysis - Tingting Liu; Chengjun Lei; Huijian Wang; Chen Xu; Wenjiao Ma; Xin He; Xiao Liang (Science Bulletin, 2024)

Insights into the generation of multiple reactive species in UV254/PMS/I− system and their roles for degradation of phenolic and non-phenolic pollutants - Zhen Tian; Yiyang Li; Lina Wang; Rui Xu; Aihua Wei; Jun He; Chengjun Wang (Journal of Water Process Engineering, 2024)

Occurrence and distribution of phycotoxins in the Antarctic Ocean - Jiale Tang; Xiuping He; Junhui Chen; Wei Cao; Tongzhu Han; Qinzeng Xu; Chengjun Sun (Marine Pollution Bulletin, 2024)

Diesel soot combustion in air-NO environment: Evolution of soot physical properties and fragmentation characteristics - Jiangjun Wei; Chengjun He; Yang Zeng (Science of The Total Environment, 2024)

Facile synthesis of multi-layer Co(OH)2/CeO2-g-C3N4 ternary synergistic heterostructure for efficient photocatalytic oxidation of NO under visible light - Zhiyu Xiao; Hainam Do; Abubakar Yusuf; Hongpeng Jia; Haolun Ma; Shanshan Jiang; Jianrong Li; Yong Sun; Chengjun Wang; Yong Ren; George Zheng Chen; Jun He (Journal of Hazardous Materials, 2024)

Differential evolution with alternation between steady monopoly and transient competition of mutation strategies - Chenxi Ye; Chengjun Li; Yang Li; Yufei Sun; Wenxuan Yang; Mingyuan Bai; Xuanyu Zhu; Jinghan Hu; Tingzi Chi; Hongbo Zhu; Luqi He (Swarm and Evolutionary Computation, 2023)

Spatial Inhomogeneity of Atmospheric CO2 Concentration and Its Uncertainty in CMIP6 Earth System Models - Chengjun Xie; Tongwen Wu; Jie Zhang; Kalli Furtado; Yumeng Zhou; Yanwu Zhang; Fanghua Wu; Weihua Jie; He Zhao; Mengzhe Zheng (Advances in Atmospheric Sciences, 2023)

Black phosphorus nanosheets enhance differentiation of neural progenitor cells for improved treatment in spinal cord injury - Fumei He; Ke Cheng; Junyang Qi; Fangjie He; Chengjun Chu; Yue Xiong; Jingxin Zhao; JiaQi Ding; FanShu Kong; ZiMeng Cao; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Coupled anaerobic methane oxidation and metal reduction in soil under elevated CO 2 - Chenchao Xu; Naifang Zhang; Kaihang Zhang; Shuyao Li; Qing Xia; Jing Xiao; Maojun Liang; Weilei Lei; Junpan He; Gaiping Chen; Chengjun Ge; Xunhua Zheng; et al. (Global Change Biology, 2023)
Continued current emissions of carbon dioxide (CO 2 ) and methane (CH 4 ) by human activities will increase global atmospheric CO 2 and CH 4 concentrations and surface temperature significantly. Fields of paddy rice, the most important form of anthropogenic wetlands, account for about 9% of anthropogenic sources of CH 4 . Elevated atmospheric CO 2 may enhance CH 4 production in rice paddies, potentially reinforcing the increase in atmospheric CH 4 . However, what is not known is whether and how elevated CO 2 influences CH 4 consumption under anoxic soil conditions in rice paddies, as the net emission of CH 4 is a balance of methanogenesis and methanotrophy. In this study, we used a long‐term free‐air CO 2 enrichment experiment to examine the impact of elevated CO 2 on the transformation of CH 4 in a paddy rice agroecosystem. We demonstrate that elevated CO 2 substantially increased anaerobic oxidation of methane (AOM) coupled to manganese and/or iron oxides reduction in the calcareous paddy soil. We further show that elevated CO 2 may stimulate the growth and metabolism of Candidatus Methanoperedens nitroreducens , which is actively involved in catalyzing AOM when coupled to metal reduction, mainly through enhancing the availability of soil CH 4 . These findings suggest that a thorough evaluation of climate‐carbon cycle feedbacks may need to consider the coupling of methane and metal cycles in natural and agricultural wetlands under future climate change scenarios.

Mercury in wetlands over 60 years: Research progress and emerging trends - Jin Zhang; Chengjun Li; Wenli Tang; Mengjie Wu; Mingying Chen; Huan He; Pei Lei; Huan Zhong (Science of The Total Environment, 2023)

Mangrove degradation retarded microplastics weathering and affected metabolic activities of microplastics-associated microbes - Hui Deng; Yuqing Zhang; Dazhen Li; Qianqian Fu; Jianxiong He; Yuanyuan Zhao; Dan Feng; Huamei Yu; Chengjun Ge (Journal of Hazardous Materials, 2023)

Black phosphorus nanosheets suppress oxidative damage of stem cells for improved neurological recovery - Fumei He; Zeqi Liu; Jian Xu; Yue Xiong; Xiaopei Zhang; Junyang Qi; Xun Lin; Chengjun Chu; Lan Shen; Gan Liu; Wenbin Deng (Chemical Engineering Journal, 2023)

Reaching the Full Potential of Machine Learning in Mitigating Environmental Impacts of Functional Materials - Ying He; Guohong Liu; Chengjun Li; Xiliang Yan (Reviews of Environmental Contamination and Toxicology, 2022)

Bioremediation of tetramethyl thiuram disulfide and resource utilization of natural rubber wastewater by WR-2 Bacillus-dominated microbial community - Dayu Zhu; Chengjun Ge; Hongfei Sun; Jun Wang; Liujing He (Environmental Science and Pollution Research, 2022)

Upper-Ocean Lateral Heat Transports in the Niño3.4 Region and Their Connection with ENSO - He Zhao; Tongwen Wu; Laurent Z. X. Li; Fanghua Wu; Weihua Jie; Xiangwen Liu; Ronghua Zhang; Chengjun Xie (Journal of Meteorological Research, 2022)

Above- and belowground biomass allocation and its regulation by plant density in six common grassland species in China - Yuanfeng Sun; Yupin Wang; Zhengbing Yan; Luoshu He; Suhui Ma; Yuhao Feng; Haojie Su; Guoping Chen; Yinping Feng; Chengjun Ji; Haihua Shen; Jingyun Fang (Journal of Plant Research, 2022)

The new chimeric chiron genes evolved essential roles in zebrafish embryonic development by regulating NAD+ levels - Chengchi Fang; Xiaoni Gan; Chengjun Zhang; Shunping He (Science China Life Sciences, 2021)

Current progress on catalytic oxidation of toluene: a review - David Murindababisha; Abubakar Yusuf; Yong Sun; Chengjun Wang; Yong Ren; Jungang Lv; Hang Xiao; George Zheng Chen; Jun He (Environmental Science and Pollution Research, 2021)

Variation of soil nitrate and bacterial diversity along soil profiles in manure disposal maize field and adjacent woodland - Yujia Cai; Ju-Pei Shen; Hong J. Di; Li-Mei Zhang; Chengjun Zhang; Ji-Zheng He (Journal of Soils and Sediments, 2020)

Photolysis of bis(2-ethylhexyl) phthalate in aqueous solutions at the presence of natural water photoreactive constituents under simulated sunlight irradiation - Qian Yu; Xiyao Xiong; Jun He; Yuegang Zuo; Yong Chen; Chengjun Wang (Environmental Science and Pollution Research, 2019)

Degradation of lipids in seasonal hypoxic seawater under different oxygen saturation - Yunhong He; Chengjun Sun; Wenjuan Li; Gui-Peng Yang; Haibing Ding (Journal of Oceanology and Limnology, 2018)

Study on immobilization of marine oil-degrading bacteria by carrier of algae materials - Yiran Zhang; Wei Gao; Faxiang Lin; Bin Han; Changfei He; Qian Li; Xiangxing Gao; Zhisong Cui; Chengjun Sun; Li Zheng (World Journal of Microbiology and Biotechnology, 2018)

The permafrost carbon inventory on the Tibetan Plateau: a new evaluation using deep sediment cores - Jinzhi Ding; Fei Li; Guibiao Yang; Leiyi Chen; Beibei Zhang; Li Liu; Kai Fang; Shuqi Qin; Yongliang Chen; Yunfeng Peng; Chengjun Ji; Honglin He; et al. (Global Change Biology, 2016)
The permafrost organic carbon ( OC ) stock is of global significance because of its large pool size and the potential positive feedback to climate warming. However, due to the lack of systematic field observations and appropriate upscaling methodologies, substantial uncertainties exist in the permafrost OC budget, which limits our understanding of the fate of frozen carbon in a warming world. In particular, the lack of comprehensive estimates of OC stocks across alpine permafrost means that current knowledge on this issue remains incomplete. Here, we evaluated the pool size and spatial variations of permafrost OC stock to 3 m depth on the Tibetan Plateau by combining systematic measurements from a substantial number of pedons ( i.e . 342 three‐metre‐deep cores and 177 50‐cm‐deep pits) with a machine learning technique ( i.e . support vector machine, SVM ). We also quantified uncertainties in permafrost carbon budget by conducting Monte Carlo simulations. Our results revealed that the combination of systematic measurements with the SVM model allowed spatially explicit estimates to be made. The OC density ( OC amount per unit area, OCD ) exhibited a decreasing trend from the south‐eastern to the north‐western plateau, with the exception that OCD in the swamp meadow was substantially higher than that in surrounding regions. Our results also demonstrated that Tibetan permafrost stored a large amount of OC in the top 3 m, with the median OC pool size being 15.31 Pg C (interquartile range: 13.03–17.77 Pg C). 44% of OC occurred in deep layers ( i.e . 100–300 cm), close to the proportion observed across the northern circumpolar permafrost region. The large carbon pool size together with significant permafrost thawing suggests a risk of carbon emissions and positive climate feedback across the Tibetan alpine permafrost region.

Comparative analyses of leaf anatomy of dicotyledonous species in Tibetan and Inner Mongolian grasslands - JianJing Ma; ChengJun Ji; Mei Han; TingFang Zhang; XueDong Yan; Dong Hu; Hui Zeng; JinSheng He (Science China Life Sciences, 2012)

Changes in topsoil carbon stock in the Tibetan grasslands between the 1980s and 2004 - YUANHE YANG; JINGYUN FANG; PETE SMITH; YANHONG TANG; ANPING CHEN; CHENGJUN JI; HUIFENG HU; SHENG RAO; KUN TAN; JIN‐SHENG HE (Global Change Biology, 2009)
Climate warming is likely inducing carbon loss from soils of northern ecosystems, but little evidence comes from large‐scale observations. Here we used data from a repeated soil survey and remote sensing vegetation index to explore changes in soil organic carbon (SOC) stock on the Tibetan Plateau during the past two decades. Our results showed that SOC stock in the top 30 cm depth in alpine grasslands on the plateau amounted to 4.4 Pg C (1 Pg=10 15 g), with an overall average of 3.9 kg C m −2 . SOC changes during 1980s–2004 were estimated at −0.6 g C m −2 yr −1 , ranging from −36.5 to 35.8 g C m −2 yr −1 at 95% confidence, indicating that SOC stock in the Tibetan alpine grasslands remained relatively stable over the sampling periods. Our findings are nonconsistent with previous reports of loss of soil C in grassland ecosystems due to the accelerated decomposition with warming. In the case of the alpine grasslands on the Tibetan Plateau studied here, we speculate that increased rates of decomposition as soils warmed during the last two decades may have been compensated by increased soil C inputs due to increased grass productivity. These results suggest that soil C stock in terrestrial ecosystems may respond differently to climate change depending on ecosystem type, regional climate pattern, and intensity of human disturbance.

Storage, patterns and controls of soil organic carbon in the Tibetan grasslands - YUANHE YANG; JINGYUN FANG; YANHONG TANG; CHENGJUN JI; CHENGYANG ZHENG; JINSHENG HE; BIAO ZHU (Global Change Biology, 2008)
The soils of the Qinghai‐Tibetan Plateau store a large amount of organic carbon, but the magnitude, spatial patterns and environmental controls of the storage are little investigated. In this study, using data of soil organic carbon (SOC) in 405 profiles collected from 135 sites across the plateau and a satellite‐based dataset of enhanced vegetation index (EVI) during 2001–2004, we estimated storage and spatial patterns of SOC in the alpine grasslands. We also explored the relationships between SOC density (soil carbon storage per area) and climatic variables and soil texture. Our results indicated that SOC storage in the top 1 m in the alpine grasslands was estimated at 7.4 Pg C (1 Pg=10 15 g), with an average density of 6.5 kg m −2 . The density of SOC decreased from the southeastern to the northwestern areas, corresponding to the precipitation gradient. The SOC density increased significantly with soil moisture, clay and silt content, but weakly with mean annual temperature. These variables could together explain about 72% of total variation in SOC density, of which 54% was attributed to soil moisture, suggesting a key role of soil moisture in shaping spatial patterns of SOC density in the alpine grasslands.